Physical activity and mental health - Clow, Angela; Edmunds, Sarah 1975- (Human Kinetics, 2014)
Written for students, researchers and professionals in exercise science, fitness and healthcare fields, this book details the factors that influence the relationship between mental health and physical activity as well as the benefits of physical activity in dealing with mental illnesses such as Alzheimer's disease, depression, and schizophrenia